2021
DOI: 10.1002/advs.202104609
|View full text |Cite
|
Sign up to set email alerts
|

A General Method to Develop Highly Environmentally Sensitive Fluorescent Probes and AIEgens

Abstract: Environmentally sensitive fluorescent probes (including AIEgens) play pivotal roles in numerous biological studies. Many of these functional materials are developed based on the twisted intramolecular charge transfer (TICT) mechanism. However, the TICT tendency of dialkylated amino groups in biocompatible main-stream fluorophores (i.e., coumarins and rhodamines) is weak, limiting their sensitivities. Herein, by replacing dialkylated amino donors with an N-methylpyrrole group to enhance TICT, a simple and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…1C); such a good relationship indicated that LDER has a twisted ICT (TICT) character. 33–35 The fluorescence intensity of LDER with dielectric constant ( ε ) of various media was also correlated, as shown in Fig. 1D.…”
Section: Resultsmentioning
confidence: 79%
“…1C); such a good relationship indicated that LDER has a twisted ICT (TICT) character. 33–35 The fluorescence intensity of LDER with dielectric constant ( ε ) of various media was also correlated, as shown in Fig. 1D.…”
Section: Resultsmentioning
confidence: 79%
“…Environmentally sensitive fluorescent probes are a class of specially designed probes with high resolution, high visibility, and excellent specificity. [ 93 ] Its fluorescence properties are affected by local environmental changes (such as acidity, alkalinity, viscosity, polarity), [ 94 ] and it plays a vital role in biological research.…”
Section: Esipt‐based Organic Nir Fluorescent Probesmentioning
confidence: 99%
“…17−19 Generally, the realization of the fluorescence turn-on mode requires the prequenching of the fluorophore before the occurrence of the specific recognition reaction between the probe and the analyte. 20 Therefore, significant efforts have been devoted to the molecular design strategies for precisely modulating the quantum yields to form the dark state of the fluorescent probe, 21 such as photoinduced electron transfer (PET), 22 fluorescence resonance energy transfer (FRET), 23 the internal filtering effect (IFE), 24 and twisted intramolecular charge transfer (TICT). 25−27 Among these methods, only TICT involves the internal rotational motion of a specific group that is driven by the change in the electron density distributions and often results in a decrease in the molecular energy accompanied by decoupling of the π-systems and nearly complete electron transfer between the two parts connecting the rotational bond.…”
mentioning
confidence: 99%